A Case Study of XR-Based Virtual Museum for Paleontology Outreach in the Brazilian Amazon - Da Silva, Letícia L. A.; D'Apolito, Carlos; Vieira, Victor A. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper presents a case study on the design and use of an XR-based virtual museum to support paleontology education and public engagement in the Brazilian Amazon. Developed with photogrammetry and immersive interaction techniques, the museum enables users to explore fossil collections typically inaccessible due to geographic and preservation constraints. Integrated into an XR extension course, the system provided students with both theoretical foundations and practical experience. The deployment culminated in a large-scale public exhibition, where students facilitated over 300 immersive sessions. Results from observations and student reflections indicate strong educational impact, skill development, and increased visibility of local scientific heritage through XR technologies.